A facile synthesis of self-healing hydrogels toward flexible quantum dot-based luminescent solar concentrators and white LEDs. Issue 35 (27th August 2019) - Hu, Xia-Hong; Liu, Ji-Dong; Du, Xiang-Yun; Cheng, Rui; Li, Qing; Chen, Su
Abstract : A multifunctional hydrogel (transparent, self-healing, and pH-sensitive) towards new flexible luminescent solar concentrators is rapidly synthesized via frontal polymerization. Abstract : Self-healing hydrogels have become a research hotspot as one of the most promising materials. Particularly, the synthesis of robust hydrogels with flexible transparent properties is highly needed towards soft flexible devices. Herein, we present a new stretchable self-healing poly(AM- co -MAH-β-CD- co -DMAPS) (AM = acrylamide, MAH-β-CD = β-cyclodextrin modified with maleic anhydride, and DMAPS = 3-dimethyl(methacryloyloxyethyl) ammonium propane sulfonate) hydrogel facilely synthesized via frontal polymerization (FP) within several minutes. The as-fabricated hydrogel exhibited pH sensitivity, good transparency and satisfactory mechanical properties with a tensile strength of up to 0.13 MPa and elongation of 600%. Based on its hydrogen bonding interaction and ionic association, excellent self-healing behavior was also achieved with a healing efficiency of up to 95%. More importantly, by introducing the appropriate amount of quantum dots (QDs), we successfully fabricated poly(AM- co -MAH-β-CD- co -DMAPS)/QD hydrogels, which showed great potential towards new flexible luminescent solar concentrators (LSCs) and white LEDs. This study not only offers a rapid synthetic route for self-healing hydrogels via FP, but also sheds great light on their wide applications toward flexible optoelectronic devices.